Effectiveness of Betel Leaf Extract Against Cercospora sp. Pathogen Causing Chili Leaf Spot In-Vitro - Mahfud, Muhammad Afif; Martosudiro, Mintarto; Choliq, Fery Abdul (University of Brawijaya, 2024)
The betel plant grows a lot and is easy to find in Indonesia. Part of the betel leaf contains antifungal compounds. This research examined the effect of betel leaf extract and its effective concentration in suppressing the pathogen Cercospora sp. in vitro. The research was conducted at the Pesticide Toxicology Laboratory, Universitas Brawijaya. Using a completely randomized design (CRD) with six treatments and five replications. The treatment was carried out in control and betel leaf extract with concentration levels of 30,000 ppm, 50,000 ppm, 100,000 ppm, 150,000 ppm, and 200,000 ppm. The results obtained were screening tests of compounds, causal tests of extracts on fungi, percentage of inhibition, and growth rate on fungi. Giving betel extract can suppress the growth of the fungus Cercospora sp., and in the 200,000 ppm extract treatment, the results were moderately effective in testing the percentage of inhibition power of the fungus Cercospora sp., which is equal to 41%.